A Neighbourhood Semantics for the Logic TK - Cezar A. Mortari; Hércules de Araújo Feitosa (Principia: An International Journal of Epistemology)
The logic TK was introduced as a propositional logic extending the classical propositional calculus with a new unary operator which interprets some conceptions of Tarski’s consequence operator. TK-algebras were introduced as models to TK. Thus, by using algebraic tools, the adequacy (soundness and completeness) of TK relatively to the TK-algebras was proved. This work presents a neighbourhood semantics for TK, which turns out to be deductively equivalent to the non-normal modal logic EMT4.